1987
DOI: 10.1111/j.1432-1033.1987.tb13631.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification of 2-hydroxyglutaryl-CoA dehydratase from Acidaminococcus fermentans. An iron-sulfur protein

Abstract: The (R)‐2‐hydroxyglutaryl‐CoA dehydratase system from Acidaminococcus fermentans was separated by chromatography of cell‐free extracts on Q‐Sepharose into two components, an activator and the actual dehydratase. The latter enzyme was further purified to homogeneity by chromatography on blue‐Sepharose. It is an iron‐sulfur protein (Mr 210000) consisting of two different polypeptides (α, Mr 55000, and β, Mr 42000) in an α2β2 structure with probably two [4Fe‐4S] centers. After activation this purified enzyme cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
3
44
1
Order By: Relevance
“…Cysteine residues are boxed, the hyphen in P9 denotes an insertion which optimizes the similarity, and the plus sign in P8 denotes an unidentified residue. and the C-terminal segment of fumarase is particularly interesting because two neighboring cysteine residues are conserved, and there is evidence relating disulfide formation in P7 to disruption of the Fe-S cluster of aconitase (22). The existence of such similarities is consistent with the view that the class I fumarases and aconitase are structurally related enzymes.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…Cysteine residues are boxed, the hyphen in P9 denotes an insertion which optimizes the similarity, and the plus sign in P8 denotes an unidentified residue. and the C-terminal segment of fumarase is particularly interesting because two neighboring cysteine residues are conserved, and there is evidence relating disulfide formation in P7 to disruption of the Fe-S cluster of aconitase (22). The existence of such similarities is consistent with the view that the class I fumarases and aconitase are structurally related enzymes.…”
Section: Methodssupporting
confidence: 69%
“…The It has previously been suggested that the class I fumarases belong to a family of iron-and sulfur-containing carboxylic acid hydrolyases which includes aconitase, maleate dehydratase, and hydroxyglutaryl-coenzyme A dehydratase (17,22,40). Evidence supporting this view comes from the relatively high instability of these enzymes, their high cysteine contents (1.5% by weight), and the presence of cysteinyl-prolyl sequences.…”
Section: Methodsmentioning
confidence: 61%
“…Finally GCDD, for which no peptide sequences are known, is also smaller (14 kDa) than the proteins encoded by either of the three OW. Another protein possibly encoded by ORF3 between gcdA and hgdA/ B could be the activator protein which is essential for activity of HGD (Schweiger et al, 1987). Two structures with obvious similarities to a terminator of transcription are located in the 3' region of the hgdB gene.…”
Section: Discussionmentioning
confidence: 99%
“…1). The oxygen-sensitive dehydratase (HgdAB), contains nonheme iron, inorganic sulfur, riboflavin and FMN [10,11]. The iron and sulfur contents as well a the kind of flavin varies among the enzymes from species (Table 1).…”
Section: Dehydration Of 2-hydroxyacyl-coa Estersmentioning
confidence: 99%